The capacity to cope with climate warming declines from temperate to tropical latitudes in two widely distributed Eucalyptus species - John E. Drake; Michael J. Aspinwall; Sebastian Pfautsch; Paul D. Rymer; Peter B. Reich; Renee A. Smith; Kristine Y. Crous; David T. Tissue; Oula Ghannoum; Mark G. Tjoelker (Global Change Biology, 2015)
As rapid climate warming creates a mismatch between forest trees and their home environment, the ability of trees to cope with warming depends on their capacity to physiologically adjust to higher temperatures. In widespread species, individual trees in cooler home climates are hypothesized to more successfully acclimate to warming than their counterparts in warmer climates that may approach thermal limits. We tested this prediction with a climate‐shift experiment in widely distributed Eucalyptus tereticornis and E. grandis using provenances originating along a ~2500 km latitudinal transect (15.5–38.0°S) in eastern Australia. We grew 21 provenances in conditions approximating summer temperatures at seed origin and warmed temperatures (+3.5 °C) using a series of climate‐controlled glasshouse bays. The effects of +3.5 °C warming strongly depended on home climate. Cool‐origin provenances responded to warming through an increase in photosynthetic capacity and total leaf area, leading to enhanced growth of 20–60%. Warm‐origin provenances, however, responded to warming through a reduction in photosynthetic capacity and total leaf area, leading to reduced growth of approximately 10%. These results suggest that there is predictable intraspecific variation in the capacity of trees to respond to warming; cool‐origin taxa are likely to benefit from warming, while warm‐origin taxa may be negatively affected.